Catalyst development for hydrocarbon production by carbon monoxide hydrogenation - Erol, Murat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
The aim of this work was the development and testing of supported rhodium catalysts for hydrocarbon production by CO hydrogenation. Four different catalysts were prepared by sequential or co-impregnation to incipient wetness of δ-Al2O3 and SiO2 supports, namely 2wt%Rh/δ-Al2O3 and 1.5wt%Rh/SiO2 in addition to La and V promoted catalysts, 1.5wt%Rh-2.6wt%La/SiO2 and 1.5wt%Rh-2.6wt%La/1.5wt%V/SiO2. Experimental plan included a parametric study of reaction temperature and contact time (W/FCO) as well as effects of support material and promoters on CO conversion. The reaction system used in the experiments consisted of mass flow controllers for gases, a down-flow micro-reactor located in a temperature-controlled furnace, traps, heated stainless steel connecting lines and two on-line gas chromatographs for feed and product analysis. Parametric studies were first conducted on 2wt%Rh/δ-Al2O3 and 1.5wt%Rh/SiO2 using a fixed inlet composition of 10 mol% CO, 20 mol% H2 and balance N2 for W/FCO ratios of 0.49-1.30 mg.min.μmol-1 at 270oC and atmospheric pressure. Subsequent experiments were performed at 230-290oC using various W/FCO ratios in the same range over both non-promoted and singly or doubly-promoted Rh/SiO2. Silica-supported catalyst samples were characterized by X-ray diffraction (XRD), surface area (BET) analysis, and environmental scanning electron microscopy (ESEM) with energy dispersive X-ray analysis (EDX) techniques. Increasing contact times, increasing reaction temperatures and addition of La or La-V promoters all improved catalytic activity (CO conversion) significantly. Among the catalyst samples tested for CO hydrogenation, doubly-promoted 1.5wt%Rh-2.6wt%La/1.5wt%V/SiO2 catalyst yielded the highest CO conversion. Since reaction tests were conducted at atmospheric pressure, methane was the major product observed in all cases.
Keywords: Hydrogenation.; Carbon monoxide.; Catalysis.